GLP-1 Receptor Activation Abrogates β-Cell Dysfunction by PKA Cα-Mediated Degradation of Thioredoxin Interacting Protein - He, Shijun; Wu, Wenyu; Wan, Yihong; Nandakumar, Kutty Selva; Cai, Xiuchao; Tang, Xiaodong; Liu, Shuwen; Yao, Xingang (Frontiers in Pharmacology, 2019)
Glucagon-like peptide 1 receptor (GLP-1R) agonist (Exendin-4) is a well-known agents to improve -cell dysfunctions via protein kinase A (PKA), but the detailed downstream molecular mechanisms are still elusive. Now we found that PKA C mediated- TXNIP phosphorylation and degradation played a vital role in the -cell protective role of exendin-4. After PKA activator (Exendin-4 or FSK) treatment, PKA C could directly interact with TXNIP by bimolecular fluorescence complementation and Co-IP assays in INS-1 cells. And PKA C overexpression decreased TXNIP level, whereas TXNIP level was largely increased in PKA C-KO -cells by CRISPR-Cas9. Interestingly, TXNIP overexpression or PKA C-KO has impaired -cell functions, including loss of insulin secretion and activation of inflammation. PKA C directly phosphorylated TXNIP at Ser307 and Ser308 positions, leading to its degradation via activation of cellular proteasome pathway. In consistent with this observation, TXNIP (S307/308A) mutant resisted the degradation effects of PKA C. However, exendin-4 affected neither TXNIP level in TXNIP (S307/308A) mutant overexpressed -cells nor in PKA C-KO -cells. Moreover, exendin-4 treatment reduced the inflammation gene expression in TXNIP overexpressed -cells, but exendin-4 treatment has no effect on the inflammation gene expression in TXNIP (S307/308A) overexpressed -cells. In conclusion, our study reveals integral role of PKA C/TXNIP signaling in pancreatic β-cells and suggests that PKA C-mediated TXNIP degradation is vital in -cell protective effects of exendin-4.